ER stress and hepatic lipid metabolism - Zhou, Huiping; Liu, Runping (Frontiers in Genetics, 2014)
The endoplasmic reticulum (ER) is an important player in regulating protein synthesis and lipid metabolism. Perturbation of ER homeostasis, referred as “ER stress”, has been linked to numerous pathological conditions, such as inflammation, cardiovascular diseases and metabolic disorders. The liver plays a central role in regulating nutrient and lipid metabolism. Accumulating evidence implicates that ER stress disrupts lipid metabolism and induces hepatic lipotoxicity. Here, we review the major ER stress signaling pathways, how ER stress contributes to the dysregulation of hepatic lipid metabolism, and the potential causative mechanisms of ER stress in hepatic lipotoxicity. Understanding the role of ER stress in hepatic metabolism may lead to the identification of new therapeutic targets for metabolic diseases.